INCREASING THE COMPETENCE OF SCHOOL PRINCIPALS IN IMPLEMENTING SCHOOL DEVELOPMENT PLANS (RPS) THROUGH THE CLCK GUIDANCE MODEL (EXAMPLE, EXERCISE, CONTROL, INDEPENDENT WORK) BASED ON INTENSIVE ASSISTANCE IN EAST SERAM DISTRICT, MALUKU PROVINCE - Jotty Sartje Haumahu (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2021)
This study aims to increase School Principals' Competence in Implementing School Development Plans (RPS) through the CLCK Guidance Model (Example, Exercise, Control, Independent Work) Based on Intensive Assistance for fourteen elementary schools' principals in East Seram District, Maluku Province. This study was built from the author's findings on school principals who implement RPS without AKPK (Professional Development Needs Analysis) but based on experiences from other schools in the vicinity. This research is a Best Practice that is carried out in 3 stages, namely OJT 1, IST, and OJT 2. After OJT 2 in the knowledge aspect, the average participant score is 83.78 with predicate B, the attitude aspect the average participant score is 86.66. with an A predicate, and the average score of participants in the skills aspect of 86.57 with an A predicate. This study's results indicate that the intensive mentoring-based CLCK guidance model (Example, Exercise, Control, Independent Work) can improve the ability of school principals in implementing RPS (School Development Plan).